EFFECT OF EXECUTIVE COMPENSATION AND BOARD GOVERNANCEON QUALITY OF SUSTAINABILITY AND FINANCIAL REPORTING ON FINANCIAL INSTITUTIONS ON IDX - Petrus Ridaryanto; Almatius Marsudi (Magister Akuntansi, Universitas Atma Jaya Makassar, 2022)
This study will examine the impact of executive compensation and board governance on the level of investment in sustainability practices and sustainability reporting quality and examine the relationship between sustainability reporting quality and financial reporting quality in financial services companies listed on the Indonesia Stock Exchange (IDX). The purpose of this study was to examine the effect of executive compensation and board governance on the quality of sustainability reporting in State-Owned Enterprises (BUMN) and financial institutions on the IDX. Observations will be made for the 2015-2019 period. The number of state-owned companies is around 120 companies and financial institutions are 95 companies. The total sample companies are 215 sample companies. The quality of sustainability reporting is measured by content analysis. This study will analyze all hypotheses using multiple regression. The results show that executive compensation and board governance have no effect on the quality of the sustainability report, and the quality of the sustainability report has a positive effect on the quality of financial reports